К ВОПРОСУ ОБ ОТРАЖЕНИИ НАИВНОЙ КАРТИНЫ МИРА В ЛЕКСИКОГРАФИИ И ЛЕКСИКОЛОГИИ (Philological Studies, 2019)
The article approaches to the decision of the problem of a naive picture of the world in native lexicologies and lexicographies. The whole complex of problems arising in this connection is the differentiation of naive and scientific concepts, the information fixed in explanatory and encyclopedic dictionaries, reflection in dictionaries of peripheral components of semantics of a word, interlanguages and ethno cultural semantic shares – finds reflection in the given work.